Penggunaan Kalimat Ekslamatif pada Mahasiswi Prodi Pendidikan Bahasa dan Sastra Indonesia di Universitas PGRI Pontianak Kelas A Sore Semester 4 - Fitri Wulansari; Jesen Jesen; Fitri Fitri; Pely Sitas Tasya (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to determine the form and meaning of explanatory sentences in the use of everyday sentences in expressing feelings or emotions. The method used in this study is a qualitative descriptive data analysis technique.These results find the form of explanatory sentences discussing the role of exclamatory sentences in conveying intense feelings such as joy, sadness, and anger. This type of sentence is an effective linguistic means to express emotions clearly. By using qualitative methods, this study explores various verbal and written expressions that contain exclamatory sentences. The findings show that exclamatory sentences not only express emotions, but also strengthen the emotional meaning in communication. Key words : daily life upgri, expressions of feelings, exclamatory sentences